Investigating the durability enhancement of recycled construction concrete through the application of nano-montmorillonite - Wei Yuan; Jie Li; Ziwei Cai (Alexandria Engineering Journal)
This study investigates the durability enhancement of recycled concrete aggregates (RCA) through the application of nano-montmorillonite (NMT), aiming to address their inferior durability compared to natural aggregates. Utilizing RCA sourced from demolished structures aged 10–30 years and NMT with a particle size of 70–100 nm, five concrete mix proportions were prepared, including a control mix with 100 % natural aggregates and four mixes with 60 % RCA replacement, varying in NMT content (1 %, 3 %, 5 % by weight). The optimal NMT dosage was identified as 3 %, where it significantly improved durability indicators. At this dosage, the 28-day compressive strength of RCA concrete was only 3–4 % lower than the control mix, and at 90 days, it matched or exceeded the control by 1–2 %. Carbonation depth reduced by 49 %, drying shrinkage by 46 %, and chloride ion ingress showed over 51 % reduction compared to the RCA mix without NMT. Electrical resistivity improved by 63 %, underscoring NMT's effectiveness in enhancing RCA concrete's durability, crucial for sustainable construction practices.